Effect of Non-Newtonian Fluid Behavior on Forced Convection from a Cluster of Four Circular Cylinders in a Duct, Part II: Bingham Plastic Fluids. Issue 1 (21st December 2021) - Trivedi, Mohit; Nirmalkar, Neelkanth; Gupta, Anoop K.; Chhabra, Rajendra P.
Abstract: Extensive results are reported on the flow and heat transfer for Bingham plastic fluids for the same configuration as in Part I over the ranges: Reynolds number ( 5 − 200 ), Prandtl number ( 1 − 100 ), and Bingham number ( 0 . 01 − 100 ) and the gap ratio ( 0 . 3 − 0 . 7 ) . At small Bingham numbers, the results deviate a little from that in Newtonian fluids except for the pockets of unyielded material. With the increasing fluid yield stress, the flow field consists of preferred flow channels between the inlet and outlet ports with high shear zones which directly influence the drag and Nusselt number. Depending upon the extent of fluid yielding, the drag on the middle cylinder can be higher by up to ∼100% or lower by up to ∼90% than that on the upstream cylinder. Similarly, the strong back flow observed at low Bingham numbers and high Reynolds numbers in the rear of the downstream cylinder leads to negative drag. In sparse arrays, the drag of upstream and downstream cylinders is comparable but that on the middle cylinder is always smaller. Similarly, the average heat transfer coefficient for each successive cylinder decreases with respect to the upstream cylinder. For the upper and downstream cylinder, this ratio is about 28-65% depending upon the kinematic conditions. In most cases, the first cylinder offers the maximum heat transfer.